2019
DOI: 10.1093/chemse/bjz030
|View full text |Cite
|
Sign up to set email alerts
|

Taste Receptor Cells in Mice Express Receptors for the Hormone Adiponectin

Abstract: Abstract The metabolic hormone adiponectin is secreted into the circulation by adipocytes and mediates key biological functions, including insulin sensitivity, adipocyte development, and fatty acid oxidation. Adiponectin is also abundant in saliva, where its functions are poorly understood. Here we report that murine taste receptor cells (TRCs) express specific adiponectin receptors and may be a target for salivary adiponectin. This is supported by the presence o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…This suggests that post‐ingestion hormone release is capable of regulating the peripheral gustatory apparatus by modulating the responsiveness of sweet stimuli (Depoortere, 2014). Receptors of adiponectin, a metabolic hormone that mediates insulin sensitivity, adipocyte development, and fatty acid oxidation, have also been found to be expressed in T1Rs, suggesting that adiponectin signaling could also impact sweet signaling (Crosson et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that post‐ingestion hormone release is capable of regulating the peripheral gustatory apparatus by modulating the responsiveness of sweet stimuli (Depoortere, 2014). Receptors of adiponectin, a metabolic hormone that mediates insulin sensitivity, adipocyte development, and fatty acid oxidation, have also been found to be expressed in T1Rs, suggesting that adiponectin signaling could also impact sweet signaling (Crosson et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, could Adipor2 dysfunction contribute to earlier physiological processes that initiate progression to BLE? Adipor1 , Adipor2 , and T‐cadherin transcripts (third adiponectin receptor) can be detected in taste receptor cells, 48 suggesting that saliva‐derived adiponectin could impact taste processing to influence eating. Also, adiponectin‐induced activation of Adipor1 expressed on dopamine neurons in the ventral tegmental area decreased spontaneous neuronal activity and firing and reversed stress‐induced increase in dopamine neuron firing and anxiety‐like behavior and Adipor1 haploinsufficiency increased dopamine neuron firing and anxiety‐like behavior 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, T-cadherin is expressed by projection neurons within the main and accessory OBs in mice [62]. Immunofluorescence analysis showed that T-cadherin was co-localized with Type 2 TRC marker phospholipase C β2 in mice [63]. Additionally, T-cadherin is expressed in the brain of adult human, including cerebral cortex, medulla, thalamus as well as midbrain, by northern blot analysis.…”
Section: Receptorsmentioning
confidence: 94%